With a little help from my friends: cognitive-behavioral skill utilization, social networks, and psychological distress in SMART Recovery group attendees. (2nd January 2020) - Raftery, Dayle; Kelly, Peter J.; Deane, Frank P.; Baker, Amanda L.; Dingle, Genevieve; Hunt, David
ABSTRACT: Objective: SMART Recovery provides cognitive behavior therapy based mutual support groups for addictions. The aim of the present study was to explore the impact of cognitive behavior skill use and the influence of a person's social network on psychological distress.Method: Paper based surveys were mailed out to 121 SMART Recovery groups across Australia. A sample of 75 SMART Recovery group members participated. Measures of social network size and composition, psychological distress and cognitive behavior skill use were collected.Results: There are high rates of self-reported mental illness within SMART Recovery respondents. Use of behavioral skills and social network influence was significantly associated with level of psychological distress.Discussion: The current results indicate that engaging in behavioral activation and having a social network of non-drinking or non-using people is associated with lower levels of psychological distress. Given the high rates of self-reported comorbid mental illness in this population, it is important research continues to explore the role of specific cognitive behavioral therapy components and social networks on recovery within mutual support groups.